Impact of risk-contingent credit and traditional credit on smallholders’ agricultural investment and productivity: Experimental evidence from Kenya - Ndegwa, Michael K.; Shee, Apurba; Ward, Patrick S.; Liu, Yanyan; Turvey, Calum G.; You, Liangzhi (International Food Policy Research Institute, 2024)
We use a multiyear, multi-arm randomized controlled trial implemented among 1,053 smallholders in Kenya to evaluate ex-ante investment and ex-post productivity and welfare benefits of two competing lending models: risk-contingent credit (RCC)—which embeds crop insurance with a loan product—and traditional credit (TC). We rely on local average treatment effects to demonstrate the effects of these alternative credit products on borrowers but report the intention-to-treat effects for their broader policy significance. Uptake of RCC increased treated households’ farm investments—specifically, adoption of chemical fertilizers—by up to 14 percent along the extensive margins and by more than 100 percent along the intensive margins, while TC’s effects were less in both magnitude and statistical significance. Neither type of credit product had a significant effect on the overall area cultivated under maize, hence enhancing agricultural intensification but not extensification. Ex-post, neither type of credit product had a strong direct effect on households’ productivity. We conclude that access to credit has potential to increase investment and productivity among smallholders, although improved productivity needs better measurement and extended intervention to be realized. To scale the potential effects of credit, derisking access to credit should be considered to expand access to credit.